Pola Perjalanan Wisatawan di Pantai Kesirat Gunungkidul - Masjhoer, Jussac Maulana; A.R., Rukmini (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2025)
The development of marine tourism destinations with numerous beaches along a single coastline, such as those in Gunungkidul, must consider tourists' spatial movement patterns. Now, tourists are shifting from crowded destinations, such as Baron Beach, to hidden gems that offer privacy and new visual experiences. This creates a significant shift in spatial movement patterns in the southern coastal region. Uncertainty in travel patterns hinders efforts to manage visitor flows and design efficient connections between destinations. This study aims to identify tourists' travel patterns to Kesirat Beach in Gunungkidul, which is becoming increasingly popular despite not offering white-sand beaches like those in other parts of Gunungkidul. A total of 97 people who encountered the researchers were given a questionnaire with closed-ended questions. The data were processed in SPSS and analyzed using a descriptive, quantitative approach. The results showed that tourist movement patterns were dominated by stopovers (78%), with short visit durations (57% for one whole day and 43% for less than one day). These results suggest that Kesirat Beach serves as a stopover point or as part of a longer travel route rather than as a final destination. Highlighting the high use of private vehicles (90%) and the preference for traveling in groups of friends (56%) underscores the importance of improving accessibility. This can help the audience feel responsible for creating inclusive and convenient access, encouraging better management of tourist flows.